2021
DOI: 10.1007/s00586-021-06895-0
|View full text |Cite
|
Sign up to set email alerts
|

Trends and patterns of thoracic intervertebral disc degeneration in symptomatic subjects: a magnetic resonance imaging analysis

Abstract: Purpose This study aimed to analyse the trends and patterns of IVD degeneration in different age groups at each level of the thoracic spine. Methods This cross-sectional MRI study included 1000 symptomatic patients who had undergone upright thoracic spine MRI. A total of 13,000 thoracic IVDs from C7/T1 to T12/L1 were classified into five grades using Pfirrmann classification. Patients were divided according to their ages into five groups (n = 200/group). The severity and pattern of IVD degeneration were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The pattern of degenerative changes in the thoracic spine and utilization of thoracic spine MRI is poorly understood and studied, especially compared to lumbar spine MRI, which has been extensively studied. 7,8,9,10,11 Multiple studies have found that lumbar spine MRI is overutilized and may lead to higher patient risk and increased healthcare costs. 8,12,13 These findings have driven the Center for Medicare and Medicaid Services (CMS) to add these ordering metrics as one of the quality measures in the Hospital Outpatient Quality Reporting Program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of degenerative changes in the thoracic spine and utilization of thoracic spine MRI is poorly understood and studied, especially compared to lumbar spine MRI, which has been extensively studied. 7,8,9,10,11 Multiple studies have found that lumbar spine MRI is overutilized and may lead to higher patient risk and increased healthcare costs. 8,12,13 These findings have driven the Center for Medicare and Medicaid Services (CMS) to add these ordering metrics as one of the quality measures in the Hospital Outpatient Quality Reporting Program.…”
Section: Discussionmentioning
confidence: 99%
“…14 A majority of symptomatic patients that undergo a thoracic spine MRI have mild disc degeneration. 10 Additionally, a reduction in unnecessary imaging studies can reduce healthcare cost.…”
Section: Discussionmentioning
confidence: 99%
“…Schneiderman grading: 1 = slight decrease in signal intensity in the nucleus pulposus; 2 = generalized hypointense nucleus; 3 = generalized hypointense nucleus with disc space narrowing. Disc hypointensity seen in Pfirrmann grades 4 and 5 was considered as DD 6,7,19. A particular spinal segment (cervical, thoracic, or lumbar) was considered to be degenerated if any disc within the segment has degenerated.…”
Section: Methodsmentioning
confidence: 99%
“…Disc hypointensity seen in Pfirrmann grades 4 and 5 was considered as DD. 6 , 7 , 19 A particular spinal segment (cervical, thoracic, or lumbar) was considered to be degenerated if any disc within the segment has degenerated. A subanalysis of subjects with thoracic DD divided participants into 2 groups, subjects with “isolated thoracic degeneration”—those with any level(s) of DD found exclusively in the thoracic spine, versus “tandem thoracic degeneration”—those with thoracic degeneration and concurrent degeneration in the cervical and/or lumbar segment.…”
Section: Methodsmentioning
confidence: 99%
“…In 2021, Mesregah et al [42] reported a cross-sectional MRI study of trends and patterns of thoracic intervertebral disc degeneration in symptomatic subjects. In this study, the total grade of IVD degeneration and the number of degenerated levels increased with increasing age.…”
Section: Prevalence Of Thoracic Degenerative Spinal Disease (Table 3)mentioning
confidence: 99%